The Dynamics of The Aula Magazine in Surabaya in 1978-2014: From Organizational News to Politics - Salma, Zamila; Hidayat, Rina Andriani (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2023)
This study is conducted to find out the process of the emergence of Aula magazine in 1978, to recognize the development of Aula magazine from 1978 to 2014, and to investigate the tendency of Aula magazine's themes during the New Order and Reformation periods. This research is structured using the historical method, comprising heuristics, criticism, interpretation, and historiography. The spatial and temporal scope is the development of Aula magazine in terms of theme tendencies from 1978 to 2014. The results as follows: Aula magazine is a monthly press media of East Java PWNU which was published on December 19th, 1978, based on the Decree of East Java PWNU. Moreover, Aula magazine from 1978 to 2014 experienced development. When it was first published, it was still a bulletin called Risalah NU and was not yet able to be published regularly, then it developed into a monthly magazine with a regular publication called Aula. It also experienced the development of theme trends during the New Order and Reformation periods. Government policies and NU organizations influenced the content of Aula magazine. During the New Order period, the content was limited to NU organizational news due to the repressive policies of the New Order government. In addition, since 1984, during the 27th NU congress in Situbondo, which resulted in a decision to return to the 1926 Khittah and not be tied to any political party, the content of Aula magazine during the New Order period was mostly dominated by organizational news. During the reformation period, The Aula magazine became more open due to government policies that were no longer repressive towards the press. In addition, the decision of Nahdlatul Ulama to establish the PKB party and the inauguration of Gus Dur, a central figure of NU, as President of the Republic of Indonesia, made the content of Aula magazine during the reformation period filled with political issues.